Olimpíadas de matemática e aliança entre o campo científico e o campo político - Souza Neto, João Alves de (Universidade Federal de São Carlos, 2012)
This paper aims to discuss the mathematical Olympiads in terms of Bourdieu's theory, seeking demonstrate valorization strategies and adoption of the field of mathematics linked to social practices related to OBMEP. The concepts of field and symbolic capital were used for analysis of research papers in order to understand the mathematical Olympiads as a strategy for appreciate mathematical fields as well as a kind of normative evaluation. This paper promotes a discussion about the alleged role of social inclusion attributed to these competitions. The research is a qualitative approach and involved the preparation of a history of the Mathematical Olympiads, literature research and document analysis. Bourdieu's theory may us understand that the field of mathematics has sufficient capital to reward and recruit talent while it naturalizes, through this process, the ideology of the gift and the inculcation of a cultural arbitrary on the technological and scientific development, which is linked to factors and interests of the economic field. This critical view for the Olympiads can contribute to the expansion of studies in the field of mathematics education in relation to school evaluation and the symbolic value of mathematics, looking this as a kind of symbolic mechanism of domination, valorization and conservation of the field of mathematics. Then OBMEP can be understood as the manifestation of an alliance between the scientifical and political field, which simultaneously establishes the mathematical culture and corroborates the economic interests.
Keywords: Matemática - estudo e ensino; Matemática - competições; Capital simbólico; Campo científico; Educação Matemática; Avaliação; Olimpíada de Matemática; OBMEP; Mathematics education; Evaluation; Scientifical field; Symbolic capital; Mathematical Olympiads; OBMEP; CIENCIAS HUMANAS::EDUCACAO